Response of tomato seed germination to several extraction techniques and magnetic field exposure treatments - Shakina, Visira Deva; Nuraini, Anne; Nurbaity, Anne (Universitas Padjadjaran, 2024)
The superior seeds are indicated by clean, good germination rate, pest and disease-free. One of the problems in providing superior tomato seeds is the presence of pulp attached to the tomato seeds, leading to less clean of seed. To remove the muscus on tomato seeds, the seeds have to be extracted. Other than seeds extraction, seeds exposure also could optimize seeds growth by increasing the metabolism of the tomato. The aim of this research is to determine the best extraction technique and magnetic field exposure for obtaining high tomato seeds germination. The complete random design used in this research consist of two factors, seeds extraction and magnetic field with three time replications. The result showed that seeds extraction for 24 hours is the best treatment for improving the maximum germination percentage, growth potential, growth rate, speed growth, uniformity index than others. Magnetic exposure at 6mT is the best treatment to improve seeds maximum growth and seeds speed growth.